Anti-C1q Antibodies as Occurring in Systemic Lupus Erythematosus Could Be Induced by an Epstein-Barr Virus-Derived Antigenic Site - Csorba, Kinga; Schirmbeck, Lucia A.; Tuncer, Eylul; Ribi, Camillo; Roux-Lombard, Pascale; Chizzolini, Carlo; Huynh-Do, Uyen; Vanhecke, Dominique; Trendelenburg, Marten (Frontiers in Immunology, 2019)
Previous infection with Epstein-Barr virus (EBV) is believed to trigger autoimmunity and to drive autoantibody generation as occurring in patients with systemic lupus erythematosus (SLE). Complement C1q and autoantibodies targeting it (anti-C1q) are also considered to be involved in the pathogenesis of SLE, independently of the impact of environmental insults. Still, the circumstances under which these autoantibodies arise remain elusive. By studying a major antigenic site of C1q targeted by anti-C1q (A08), we aimed to determine environmental factors and possible mechanisms leading to the development of anti-C1q. First, we determined antigenic residues of A08 that were critical for the binding of anti-C1q; importantly, we found the binding to depend on amino-acid-identity. Anti-C1q of SLE patients targeting these critical antigenic residues specifically cross-reacted with the EBV-related EBNA-1 (Epstein-Barr virus nuclear antigen 1)-derived peptide EBNA348. In a cohort of 180 SLE patients we confirmed that patients that were seropositive for EBV and recognized the EBNA348 peptide had increased levels of anti-A08 and anti-C1q, respectively. The correlation of anti-EBNA348 with anti-A08 levels was stronger in SLE patients than in matched healthy controls. Finally, EBNA348 peptide-immunization of C1q-/- mice induced the generation of cross-reactive antibodies which recognized both the A08 epitope of C1q and intact C1q. These findings suggest that anti-C1q in SLE patients could be induced by an EBV-derived epitope through molecular mimicry, thereby further supporting the pathogenic role of EBV in the development of SLE. Considering the role of C1q and anti-C1q, modifying the anti-EBV response might be a promising strategy to improve the course of the disease.